Review: Familiarity to Vision Rehabilitation Process - Nasser Sadegh-Pour (University of Social Welfare and Rehabilitation Sciences, 2006)
Considering the numbers of low vision patients who have been visited and treated in eye clinics, sometimes there is no exact treatment to increase their visual acuity. Therefore, the necessity to pay attention to vision rehabilitation for them is strongly felt. The aims of this essay are to define vision rehabilitation and its process in relevant centers (called Low Vision Clinic).The statistic of low vision people is reported and the method of collecting data is described. Standard definition, causes of low vision and related diseases (congenital, heredity, acquired...) are explained. In addition, low vision aids and role of test and prescription are discussed. Sometimes ophthalmologists and optometrists can not exactly cure patient to raise their V.A because there is no treatment or drug or ordinary glasses. In these cases the clients should refer to low vision clinic and visit low vision specialist on vision rehabilitation process. After primary evaluation they are tested completely and at the end are prescribed proper low vision aid and also provided with advice in relation to career, education role and training techniques especially in children. At the last part of present dissertation, some examples are provided to show effectiveness of vision rehabilitation and low vision aid among the clients in different countries.